When Doctors Don't Tie: Hierarchical Medicalization, Reproduction, and Sterilization in Brazil. (12th September 2018) - Edu, Ugo Felicia
Abstract: Drawing on ethnographic fieldwork among black women, medical personnel, and activists in Brazil, this article highlights the implications of hierarchical medicalization. I show that the prioritization of particular forms of medicalized contraception for women located differentially in society enables different relations, political positions, and mobility. Denial of a tubal ligation in favor of modern reversible contraceptives, in a context of inequitable distribution, can perpetuate social stratification. This work contributes to literature exploring the complexity of medicalization and its relationship with society via reproduction.